A rhodanine flanked nonfullerene acceptor for solution-processed organic photovoltaics - Holliday,S; Ashraf,RS; Nielsen,CB; Kirkus,M; Roehr,JA; Tan,C-H; Collado-Fregoso,E; Knall,A-C; Durrant,JR; Nelson,J; McCulloch,I (Journal of the American Chemical Society, 2015)
A novel small molecule, FBR, bearing 3-ethylrhodanine flanking groups was synthesized as a nonfullerene electron acceptor for solution-processed bulk heterojunction organic photovoltaics (OPV). A straightforward synthesis route was employed, offering the potential for large scale preparation of this material. Inverted OPV devices employing poly(3-hexylthiophene) (P3HT) as the donor polymer and FBR as the acceptor gave power conversion efficiencies (PCE) up to 4.1%. Transient and steady state optical spectroscopies indicated efficient, ultrafast charge generation and efficient photocurrent generation from both donor and acceptor. Ultrafast transient absorption spectroscopy was used to investigate polaron generation efficiency as well as recombination dynamics. It was determined that the P3HT:FBR blend is highly intermixed, leading to increased charge generation relative to comparative devices with P3HT:PC60BM, but also faster recombination due to a nonideal morphology in which, in contrast to P3HT:PC60BM devices, the acceptor does not aggregate enough to create appropriate percolation pathways that prevent fast nongeminate recombination. Despite this nonoptimal morphology the P3HT:FBR devices exhibit better performance than P3HT:PC60BM devices, used as control, demonstrating that this acceptor shows great promise for further optimization.